2014
DOI: 10.1016/j.commatsci.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo simulation of the effective diffusivity in grain boundary networks

Abstract: The effective diffusivity in grain boundary networks of polycrystalline materials is evaluated using a kinetic Monte Carlo model. This model connects the atomic hopping processes with the coarse-grained diffusion so that the macroscopic simulations can be conducted without the need to resolve atomic details. The effects of various properties of the grain boundary network on the effective diffusivity have been examined, including grain size, two-vs. three-dimensional networks, and distribution of grain boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The time of interstitials diffusion along dislocation grid to reach edges of GBs is denoted as t sink and it has the units of seconds. To determine t sink , we employ a similar strategy for coarse grained modeling of GBs as implemented in ref 36 . First of all, we use the nudged elastic band (NEB) method 37 to obtain the energy landscape for interstitials diffusion along a dislocation lines between two intersections of dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…The time of interstitials diffusion along dislocation grid to reach edges of GBs is denoted as t sink and it has the units of seconds. To determine t sink , we employ a similar strategy for coarse grained modeling of GBs as implemented in ref 36 . First of all, we use the nudged elastic band (NEB) method 37 to obtain the energy landscape for interstitials diffusion along a dislocation lines between two intersections of dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated in Ref. [32] that with the appropriate hopping rate, the kMC model with coarse-grained hops yields the same effective diffusivity as a model with atomic resolution. Thirdly, the difference between the diffusion of Ag along GB junctions and within GB planes is ignored here.…”
Section: Kinetic Monte Carlo Modelmentioning
confidence: 99%
“…It is emphasized here that although the diffusivity ratio in our model can be as large as 10 2 or 10 3 , it does not mean that the effective diffusivity D eff will vary 2 or 3 orders of magnitude. The actual fluctuation of D eff , which is one of the main interests of this study, remains to be examined because D eff is not only dependent on D L and D H , but it is also affected by f H , as well as by the connectivity of GBs [32,37]. We note that by fitting the values of diffusivities to release data from Refs.…”
Section: Grain Boundary Diffusion Of Ag In Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the movement does not change the diffusion speed in regime C. This is not true for Regime B, where the penetration depth is lower for a moving grain boundary [174]. Deng et al studied the diffusion in Regime C for more than one type of grain boundary [175]. They studied how grain boundaries with fast and slow diffusion lead to an effective diffusion coefficient of the overall grain boundary network (the effective diffusion coefficient should not be confused with D ef f in Regime A).…”
Section: 23)mentioning
confidence: 99%